Motivasi Belajar Dalam Pandangan Al-Qur’an - Yuliana Siregar (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2022)
This study aims to analyze the motivation to learn in the view of the Qur'an. This research uses the literature study method by searching for written sources in books, journals and interpretations. The results showed that Motivation is a force or impulse from within a person that moves individuals to do or do something both positive and negative in nature. In the context of learning a person clearly needs motivation that will determine his success in acquiring knowledge. Modern theory says that such motivation comes from within a person because of the high spirit of achievement. Meanwhile, the motivation that comes from outside is as self-actualization. The Qur'an states that the motivation to learn is done by a person because he wants to improve thinking skills, become an enlightened person and get a high degree.